1968
DOI: 10.1002/ijc.2910030516
|View full text |Cite
|
Sign up to set email alerts
|

Tumor fluid thromboplastin activity

Abstract: The thromboplastin activity of T‐241 Lewis sarcoma peripheral fluid and control subcutaneous fluid in C57BL/6Ja male mice was measured, using a calcium reconstitution assay. The material was collected in Millipore filter chambers. At low dilutions of the collected material there was a statistically significant increase in clotting activity of the tumor peripheral fluid. The calcium ion concentration of the collected fluid was also measured. It was also noted that gels were found more frequently, and in larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1969
1969
1992
1992

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The presence of increased thromboplastin activity in the peripheral fluids of the Lewis Sarcoma T-241 in vivo, over comparable " normal " tissue fluids, has been demonstrated (Frank and Holyoke, 1968). The present experiments made in tissue culture also demonstrate thromboplastin activity released by the T-241 Lewis Sarcoma cells into their environments.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The presence of increased thromboplastin activity in the peripheral fluids of the Lewis Sarcoma T-241 in vivo, over comparable " normal " tissue fluids, has been demonstrated (Frank and Holyoke, 1968). The present experiments made in tissue culture also demonstrate thromboplastin activity released by the T-241 Lewis Sarcoma cells into their environments.…”
Section: Discussionsupporting
confidence: 74%
“…Thornes (1961), demonstrated that incubation of tumor slices in saline resulted in the release of thromboplastin activity into the medium. Using the Lewis Sarcoma, T-241, Frank and Holyoke (1968) demonstrated by means of small millipore collection chambers in vivo, that tissue fluid samples collected from tumor periphery showed more thromboplastin activity than samples from normal subcutaneous tissues.…”
mentioning
confidence: 99%
“…There is an extensive literature describing procoagulant activities (PCAs) of various types associated with disrupted tumor cells (3,12,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102). However, the biological significance of this finding is, in our view, open to serious question: it is unclear how much of the PCA expressed by broken cells in vitro would be expressed by living tumor cells in vivo; also extracts of normal as well as malignant cells may exhibit PCA (103)(104)(105).…”
Section: Tumor Procoagulantsmentioning
confidence: 99%
“…The specific activities of PCA1o and of several plasma membrane-derived enzymes-5'-nucleotidase, ouabain-sensitive Na+-K+-adenosinetriphosphatase, and phosphodiesterase I-were much greater in ultracentrifuge pellets of culture supernatants than in line 10 cell homogenates (10,70,11, and 122 times greater, respectively) or cell-free culture supematants (4, > 315, 6, and 7 times greater, respectively). Enzyme markers for endoplasmic reticulum (NADH oxidoreductase) and lysosomes (,-D-glucuronidase) were only detected at low levels in culture fluids and remained in the l00,OOOg supernatant.…”
mentioning
confidence: 90%